Peran Guru Sebagai Motivator dalam Mengembangkan Minat Siswa pada Ekstrakurikuler Seni Tari di SD Negeri 75 Kota Bengkulu - Sumarsih, Indriastuty; Anggraini, Dwi; Kurniawati, Ike (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2024)
This study aims to describe the role of the teacher as a motivator in developing student interest in extracurricular dance at SD Negeri 75 Bengkulu City. This type of research is qualitative research with descriptive methods. With the research subject being the dance extracurricular supervisor teacher and students who take part in dance extracurricular activities totaling 12 students. The research instruments used are observation guidelines, interview guidelines and documentation guidelines. Data collection techniques in this study used observation, interviews and documentation. The data analysis technique used is data collection, data condensation, data presentation and conclusion drawing. The results of this study indicate that the teacher carries out his role as a motivator in providing direction, encouraging and giving praise/reward. Teachers provide direction to students by directing students to come to practice, directing student movements, and directing students to have knowledge about dance. The teacher also encourages students by giving words of encouragement and showing enthusiasm for dance. Teachers also give praise/rewards to students who diligently practice or memorize dance movements. The conclusion in this study is that the teacher shows his role as a motivator who can develop students' interest in extracurricular dance. Thus students who have an interest in dance cannot be separated from the role of the teacher.